The role of linagliptin, a selective dipeptidyl peptidase-4 inhibitor, in the morphine rewarding effects in rats. (February 2020) - Łupina, Małgorzata; Talarek, Sylwia; Kotlińska, Jolanta; Gibuła-Tarłowska, Ewa; Listos, Piotr; Listos, Joanna
Abstract: Linagliptin is a selective dipeptidyl peptidase-4 (DPP-4) inhibitor which suppresses the rapid degradation of endogenous glucagon-like peptide-1 (GLP-1). In clinical practice, it is used as an antidiabetic drug, but recent studies have confirmed its role in the activity of the central nervous system (CNS). The reported study focused on the role of linagliptin (10 and 20 mg/kg, ip) in the morphine rewarding effect, analyzing how the agent had influenced the conditioned place preference (CPP) in rats via the expression, acquisition, extinction and reinstatement of the morphine rewarding effect. The obtained results clearly demonstrated linagliptin to inhibit the expression and acquisition, to accelerate the extinction and, eventually, to reduce the reinstatement of morphine-induced CPP. The undertaken experiments significantly extended our knowledge on the mechanisms behind the morphine rewarding effect. Highlights: Linagliptin inhibited the expression of the morphine rewarding effect, in rats. Linagliptin reduced the acquisition of the morphine rewarding effect, in rats. Challenge dose of morphine reinstated the morphine-conditioned place preference, in rats. Linagliptin inhibited the reinstatement of the morphine rewarding effect, in rats. Linagliptin accelerated the extinction of the morphine rewarding effect, in rats.